Nano-Crystalline Tricalcium Silicate Bio-cement: Fabrication, Characterization and Antibacterial Activity - El-Hamid, H. K. Abd (Current Innovations in Chemical and Materials Sciences Vol. 9, 2024)
The synthesis of tricalcium silicate phases in nanoscale particles was achieved by two distinct techniques: the solid-state reaction and the sol-gel approach. The solid-state procedure depends on the direct firing of a mixture of molar ratios of ultra-pure calcium carbonate and silicon dioxide at around 1500°C, whereas the sol-gel method is dependent on when calcium nitrate tetrahydrate and tetraethyl orthosilicate combine at pH = 4.5, a C3S gel is created. An investigation was conducted to compare the two produced powders using various techniques such as infrared spectroscopy, scanning electron microscopy (SEM), pH values, calcium ion concentration, micro-hardness test, and X-ray diffraction analysis. The agar diffusion method is used to assess the antibacterial activity of free-released Ca2+ ions. The results show that compared to the sample made using a solid-state process, the C3S powder synthesized using the sol-gel approach has higher chemical reactivity with an increasing rate of hydration reaction. The sol-gel sample has a higher pH and calcium ion concentration, a more alkaline hydration medium, improved hardness values, and a faster setting time. The test sol-gel sample's higher influence from Ca ions generated throughout the hydration process allowed it to demonstrate substantially better antibacterial activity.